Cytotoxicity of epoxy-encapsulated Al-doped YIG nanoparticles in MG63 osteoblast cells - Ortega, P. P. [UNESP]; Acero, G. [UNESP]; Garcia, F. G.; Longo, E.; Simões, A. Z. [UNESP] (Elsevier, 2025)
In this study, the structural, magnetic, and cytotoxicity towards MG63 osteoblasts-like cells of epoxy/Y3Fe5O12: 1.6 wt% Al (YIG) nanoparticles were investigated. The nanoparticles crystallized in the garnet structured of YIG without secondary phases. The magnetization curve indicated the sample is superparamagnetic, with reduced residual magnetization and coercivity field (0.80 emu/g and 3.7 mT) and magnetization saturation of 24.47 emu/g, which are desirable characteristics for biomedical applications. Cytotoxic studies were performed to investigate if the nanoparticle encapsulation with DGEBA and IPD were effective in promoting cell viability, using MG63 osteoblast-like cells as a model. The results showed cell viability of >90 %, indicating that the Al-doped YIG encapsulation with DGEBA and IPD are promising methods to enhance its biocompatibility aiming in vivo applications, such as hyperthermia treatment.
Keywords: Aluminum substituted YIG; Epoxy polymer; MG63 cells; Polymeric Precursor Method